2015
DOI: 10.1111/jopr.12325
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Modified Poly‐Ether‐Ether‐Ketone (PEEK) as an Alternative Framework Material for Removable Dental Prostheses. A Clinical Report

Abstract: This clinical report presents a modified poly-ether-ether-ketone (PEEK) as an alternative material for the fabrication of distal extension removable dental prosthesis (RDP) frameworks. This material can be used for patients allergic to metals, or who dislike the metallic taste, the weight, and the unpleasant metal display of the denture framework and retentive clasps. This modified PEEK material, known as BioHPP, is a biocompatible, nonallergic, rigid material, with flexibility comparable to bone, high polishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
193
1
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(207 citation statements)
references
References 18 publications
2
193
1
11
Order By: Relevance
“…For this reason, many studies have investigated the material regarding the relevant properties, e.g., wear resistance [6], fracture load [7,8,9], retention load and retention forces [10,11], hardness [12], flexural behavior [13], and discoloration [14]. PEEK has thus been proven to be a suitable material for fixed dental prostheses (FDPs) [15,16,17] and long-term restorations [4,6,10,11,12,13,18]. …”
Section: Introductionmentioning
confidence: 99%
“…For this reason, many studies have investigated the material regarding the relevant properties, e.g., wear resistance [6], fracture load [7,8,9], retention load and retention forces [10,11], hardness [12], flexural behavior [13], and discoloration [14]. PEEK has thus been proven to be a suitable material for fixed dental prostheses (FDPs) [15,16,17] and long-term restorations [4,6,10,11,12,13,18]. …”
Section: Introductionmentioning
confidence: 99%
“…Additional advantages of this polymer are elimination of allergic reactions and metallic taste, high polishing qualities, low plaque affinity, and good wear resistance . An in vivo study reported that PEEK should probably be considered as an alternative removable partial denture framework material for patients with taste sensitivity or allergies to conventional Cr‐Co frameworks . Although PEEK has significant advantages for dental applications, difficulties in establishing a strong and durable adhesion to dental material are the major clinical disadvantage .…”
mentioning
confidence: 99%
“…Five were clinical reports [2,6,8,18,24] and 35 were papers on PEEK surface treatments [13][14][15][16][17] how the bioactivity of PEEK can be improved [1,21]; the characteristics of CFR-PEEK [3,7,[19][20]; the biocompatibility of PEEK [5]; PEEK applications [4,8,[10][11]30]; PEEK biofilm formation [22,[31][32][33][34], PEEK as an abutment material and as an implant material [12,23,[25][26][27][28][29]35,40] and the use of CAD-CAM with PEEK [36][37][38][39]. …”
Section: Literature Search and Resultsmentioning
confidence: 99%
“…It is also wear-resistant, compatible with many reinforcing agents (such as glass and carbon fibers), stable at temperatures exceeding 300°C. This polymer is very biocompatible in vivo and in vitro, does not cause toxic or mutagenic effects; therefore it is indicative in patients allergic to titanium [1,[4][5][6]. Notwithstanding, Maldonado-Naranjo et al described a case report with clinical evidence of allergy to PEEK.…”
Section: Structure and Properties Of Peekmentioning
confidence: 99%
See 1 more Smart Citation